Keputusan Mahasiswa Universitas “X” Bandung Untuk Merokok Di Lingkungan Kampus Yang Dipengaruhi Oleh Faktor Sosial - Ayuningtyas Hapsari; Alfath Haikal Muhammad (Universitas Multimedia Nusantara, 2018)
Indonesia is the country with the highest number of teen smokers in the world. About 80% of smokers in Indonesia start the habit before the age of 19 years. Based on the results of a pre-survey of 10 students that there are still many who violate the rules despite the existing prohibition to not smoke in public places at the University of